Dissemination of Multidrug-Resistant Commensal Escherichia coli in Feedlot Lambs in Southeastern Brazil - Gozi, Katia Suemi; Froes, Juliana Rodrigues; Deus Ajude, Luana Perpetua Tobias; da Silva, Caroline Rodrigues; Baptista, Rafaela Speranza; Peiró, Juliana Regina; Marinho, Marcia; Mendes, Luiz Claudio Nogueira; Nogueira, Mara Corrêa Lelles; Casella, Tiago (Frontiers in Microbiology, 2019)
Antimicrobial resistance (AR) is a public health issue since it limits the choices to treat infections by Escherichia coli in humans and animals. In Brazil, the ovine meat market has grown in recent years, but studies about AR in sheep are still scarce. Thus, this study aims to investigate the presence of AR in E. coli isolated from lambs during feedlot. To this end, feces from 112 lambs with 2 months of age, after weaning, were collected on the first day of the animals in the feedlot (day 0), and on the last day before slaughtering (day 42). Isolates were selected in MacConkey agar supplemented with 4 mg/L of ceftiofur and identified by biochemical methods. Isolates were submitted to antimicrobial susceptibility test by disc-diffusion, and PCR to investigate genes for phylogenetic group, for virulence determinants and for resistance to the several antimicrobial classes tested. The genetic localization of the bla genes detected was elucidated by S1-PFGE followed by Southern blot-hybridizations. The isolates were typed by XbaI-PFGE and MLST methods. Seventy-eight E. coli were isolated from 8/112 (7.1%) animals on day 0, and from 55/112 (49.1%) animals on day 42. Since only fimH was present in almost all E. coli (97.4%) as virulence gene, and also 88.5% belonged to phylogroups B1 or A, we consider that isolates represent intestinal commensal bacteria. The dendrogram separated the 78 non-virulent isolates in 7 clusters, two of which comprised 50 E. coli lineages belonging to ST1727 and ST3994 recovered on day 42 commonly harboring the genotype blaCMY-2-aac(3)-IIa -tetA-sul1-sul2-floR-cmlA. Special attention should be given to the presence of blaCTX-M-15, a worldwide gene spread, and blaCTX-M-14, a hitherto undetected gene in Enterobacteriaceae from food-producing animals in Brazil. Importantly, E. coli lineages and plasmids carrying bla genes detected here have already been reported as sources of infection in humans either from animals, food, or the environment, which raises public health concerns. Hence, two types of commensal E. coli carrying important AR genes clearly prevailed during feedlot, but lambs are also reservoirs of bacteria carrying important AR genes such as blaCTX-M-14 and blaCTX-M-15, mostly related to antimicrobial treatment failure.